2022
DOI: 10.3390/molecules27123929
|View full text |Cite
|
Sign up to set email alerts
|

Dipeptidyl Peptidase 3 Activity as a Promising Biomarker of Bone Fragility in Postmenopausal Women

Abstract: The dipeptidyl peptidase 3 (Dpp3) is a ubiquitous zinc-dependent aminopeptidase, participating in the activation or degradation of signaling peptides and in the Keap1–Nrf2 antioxidant pathway. The absence of Dpp3 in the Dpp3 knockout mouse model causes increased osteoclast activity, altered osteogenic function, sustained oxidative stress in the bone tissue, and bone loss. We aimed to assess the association of Dpp3 activity with bone fragility in postmenopausal osteoporosis and the impact of denosumab on enzyma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…In conclusion, a non-conventional analysis of bone uncovered a possible metabolic alteration in this tissue in the absence of Dpp3. A recent clinical study proposed DPP3 as a bone protective factor, by showing significant association with femoral neck bone mineral density in post-menopausal osteoporotic women before treatment and significant reduction in patients compared to controls ( Menale et al, 2022 ). Taken together, these findings will deserve further investigation, also considering their possible translational relevance for human bone pathophysiology.…”
Section: Resultsmentioning
confidence: 99%
“…In conclusion, a non-conventional analysis of bone uncovered a possible metabolic alteration in this tissue in the absence of Dpp3. A recent clinical study proposed DPP3 as a bone protective factor, by showing significant association with femoral neck bone mineral density in post-menopausal osteoporotic women before treatment and significant reduction in patients compared to controls ( Menale et al, 2022 ). Taken together, these findings will deserve further investigation, also considering their possible translational relevance for human bone pathophysiology.…”
Section: Resultsmentioning
confidence: 99%
“…A recent clinical trial also found a close relationship between progressive cell death and the high level of DPP3 in plasma during the shock of various etiologies ( 72 ). It is precisely the wide distribution of DPP3 inside and outside cells that make it participating in various physiological and pathological processes, such as oxidative stress ( 73 75 ), RAS over-activation ( 45 , 76 ), and inflammation ( 77 , 78 ). Therefore, the above evidence fully indicates that DPP3 is widely distributed in multiple organisms and tissues and may have a broader range of biological functions.…”
Section: Biological Propertiesmentioning
confidence: 99%